Unlocking University Students' Perceptions: What Defines Effective EFL Writing Instructors in the Digital Age - Ribahan; Ariawan, Soni (Forum for Linguistic Studies, 2025)
This study aimed to investigate university students' perceptions of the essential qualities of effective EFL writing instructors in the digital age. Data were collected from 134 students through a structured Likert-scale questionnaire. Descriptive statistical analysis, containing mean and standard deviation, was employed to analyze the data regarding five main qualities: pedagogical competence, linguistic competence, interpersonal skills, motivational strategies, and adaptability to technology. The results showed that students highly appreciate clear and constructive feedback, diverse instructional approaches, and incorporation of digital resources. Linguistic competence, including explicit grammar instruction and effective modeling of writing techniques, is also considered essential. Additionally, strong interpersonal skills contribute to a supportive learning environment, while motivational strategies, including acknowledging students' progress and achievement, help maintain engagement. Adaptability to technology is crucial, as students value instructors who integrate digital tools and enhance feedback through technology. The most significant quality that students identified was linguistic competence dealing with theinstructors' ability to articulate grammar, coherence, and rhetorical structures with precision. Interpersonal skills were also highly rated, emphasizing the importance of a positive classroom environment and personalized assistance. Effective feedback delivery and instructional variation were facilitated by pedagogical competence, while motivational strategies were essential for maintaining engagement through the progress recognition. Finally, the significance of incorporating digital tools into writing instruction was underscored by the necessity of technological advancements adaptation. The results of the present study highlight the need for training programs that blend digital and interpersonal skills. Future studies should examine how these qualities directly impact student writing outcomes.